(untitled) (Global Journal of Human-Social Science, 2015)
The post-colonial Nigerian state imbibed the gory traits of the colonial state; it served mostly as a tool for economic exploitation. The emergent elites saw governance solely, as a means for predation, thus, excluding the masses and weaker political elites. Oil further deepened the chasm, as, contending elites used oil revenues to fund and reproduce their dominance rather than provide public goods; utterly disconnecting the elite from the people. To gain political power; the means of predation, the elite resorted to votebuying, and as, the electoral process became more competitive, they turned to even more weird ways; recruitment and arming of youths to secure votes; with unintended costs. The paper argues that the Boko Haram, which for years has caused dire insecurity in Nigeria’s North East is an unintended cost of elite predatory antics. The paper concludes that except there is vigorous deference of elite predisposition to predation, their actions may utterly emasculate national cohesion.